A genre neglected in juvenile literature: essay - Namık Kemal ŞAHBAZ (İnönü Üniversitesi Eğitim Fakültesi Dergisi)
Informative texts are as functional as the fictional ones for a child’s cognitive, linguistic, and social development. In Turkey, essay as an informative literary genre has been neglected in the juvenile literature. In this respect, the genre of essay in juvenile literature and the characteristics of the essays for children are examined based on the Turkish course books and juvenile literature anthology. Finally, an example essay extract for children was given.